2000
DOI: 10.1614/0890-037x(2000)014[0156:whoscn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Hosts of Soybean Cyst Nematode (Heterodera glycines) in Ohio1

Abstract: In greenhouse experiments, Ohio accessions of 22 weed species representing 13 dicot families were screened as alternative hosts of soybean cyst nematode (SCN, Heterodera glycines). Purple deadnettle (Lamium purpureum), henbit (Lamium amplexicaule), field pennycress (Thlaspi arvense), shepherd's-purse (Capsella bursa-pastoris), and a susceptible soybean (Glycine max) cultivar produced SCN population densities of 510, 155, 73, 1, and 366 cysts/450 cm3 soil, respectively, 5 wk after inoculation with eggs from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 5 publications
2
68
1
Order By: Relevance
“…T. arvense has been reported as a host for the sugar beet eel worm or cyst nematode, Heterodera schachtii Schmidt, in Saskatchewan (reviewed in Best and McIntyre 1975). In a greenhouse study, Venkatesh et al (2000) found that an Ohio population of T. arvense could serve as an alternative host of soybean cyst nematode (Heterodera glycines Ichinohe).…”
Section: Response To Herbivory Disease and Higher Plant Parasitesmentioning
confidence: 99%
“…T. arvense has been reported as a host for the sugar beet eel worm or cyst nematode, Heterodera schachtii Schmidt, in Saskatchewan (reviewed in Best and McIntyre 1975). In a greenhouse study, Venkatesh et al (2000) found that an Ohio population of T. arvense could serve as an alternative host of soybean cyst nematode (Heterodera glycines Ichinohe).…”
Section: Response To Herbivory Disease and Higher Plant Parasitesmentioning
confidence: 99%
“…Soybean cyst nematode (SCN, Heterodera glycines ) commonly infests soybean ( Glycine max ) fields in the United States and is a threat to profitable soybean production. In a greenhouse experiment, purple deadnettle ( Lamium purpureum ) was identified as an excellent host for SCN (4). Purple deadnettle (Fig.…”
mentioning
confidence: 99%
“…5), and shepherd's‐purse [ Capsella bursa‐pastoris (L.) Medik] (Fig. 6) were shown to support SCN reproduction (52). Earlier reports had identified common chickweed [ Stellaria media (L.) Vill.]…”
Section: Weeds As Alternative Hosts Of Scnmentioning
confidence: 99%
“…2). Venkatesh et al (52) reported that on susceptible soybeans SCN (race 3) cyst population densities were 366 per 450 cm 3 of soil. Purple deadnettle (510 per 450 cm 3 ), henbit (155 per 450 cm 3 ), field pennycress (73 per 450 cm 3 ), and shepherd's purse (1 per 450 cm 3 ) were also reported to support SCN reproduction.…”
Section: Potential Management Implicationsmentioning
confidence: 99%